2018
DOI: 10.1021/acs.jafc.8b00127
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Biofortification in Rice (Oryza sativa L.) Sprouting: Effects on Se Yield and Nutritional Traits with Focus on Phenolic Acid Profile

Abstract: The contents of total Se and of inorganic and organic Se species, as well as the contents of proteins, chlorophylls, carotenoids, and phenolic acids, were measured in 10-day old sprouts of rice ( Oryza sativa L.) obtained with increasing levels (15, 45, 135, and 405 mg Se L) of sodium selenite and sodium selenate and with distilled water as control. Increasing Se levels increased organic and inorganic Se contents of sprouts, as well as the content of phenolic acids, especially in their soluble conjugated forms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
54
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 53 publications
9
54
1
Order By: Relevance
“…The content of phenolic acids varied according to the genotype and the Se dose in a specific way. In coriander and tatsoi, our results are consistent with what was found by D'amato et al [49], which reported a rise in phenolic compounds in rice sprouts as the applied Se dose increased. Likewise, Se treatments in the range 0.25-0.50 mg L −1 (3.2-6.4 µM Se) were shown to increase the total phenol content in wheat microgreen extract [10].…”
Section: Phenolic Compounds Profilingsupporting
confidence: 93%
See 3 more Smart Citations
“…The content of phenolic acids varied according to the genotype and the Se dose in a specific way. In coriander and tatsoi, our results are consistent with what was found by D'amato et al [49], which reported a rise in phenolic compounds in rice sprouts as the applied Se dose increased. Likewise, Se treatments in the range 0.25-0.50 mg L −1 (3.2-6.4 µM Se) were shown to increase the total phenol content in wheat microgreen extract [10].…”
Section: Phenolic Compounds Profilingsupporting
confidence: 93%
“…The non-significant effect on yield observed in green and purple basil was in agreement with previous studies on Se-biofortified microgreens [9] and mature plants [26] of basil. On the other hand, the beneficial Se effect found on the yield of coriander and tatsoi was consistent with the growth-promoting response to low Se doses demonstrated in previous works on rice sprouts [49] and mature plants of Indian mustard [50], ryegrass [51], spinach [52], and lettuce [53]. It was demonstrated that Se at low concentrations can stimulate plant growth, enhance photosynthesis, and support the homeostasis of essential nutrients [54].…”
Section: Fresh Biomass Yield and Dry Matter Contentsupporting
confidence: 89%
See 2 more Smart Citations
“…Experiments conducted on broccoli, radish, alfalfa and mung bean have shown that microgreens can be biofortified with iron and magnesium, whereas the biofortification of microgreens with Se has not yet been investigated. On the other hand, Se enrichment of sprouts has been studied in Oryza sativa Cicer aretinum , Brassica oleracea, Raphanus sativus and Allium cepa …”
Section: Introductionmentioning
confidence: 99%